2021
DOI: 10.1051/limn/2021012
|View full text |Cite
|
Sign up to set email alerts
|

Ecological status estimation of eight creeks in the Lake Sapanca Basin (Sakarya, Turkey) using diatom indices

Abstract: It is important to determine the water quality of the creeks in the Lake Sapanca basin since it is used for drinking water supply. For this purpose, environmental parameters and diatom assemblages as biological quality components were investigated to determine the ecological status of eight creeks with monthly intervals between March 2015 and February 2016. During the studied period, 19 taxa increased their relative abundance higher than 30% in at least one sample and showed a different seasonal pattern. Main … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…Except for E. turgida var. granulata, all of these species were found in lowland rivers of the Sakarya Basin (Çetin & Demir, 2019;Sevindik et al, 2021;Solak et al, 2020;Tokatlı & Dayıo glu, 2011;Yüce & Gönülol, 2016) Tokatlı & Dayıo glu, 2011). The following species were identified as dominant: U. ulna in Murat Stream (Tokatlı & Dayıo glu, 2011) and in Kurtköy Creek (Sevindik et al, 2021), M. varians, M. circulare, N. radiosa and U. ulna in Felent Creek , N. radiosa in lower Sakarya River (Yüce & Gönülol, 2016) and M. varians, M. circulare and U. ulna in the upper Sakarya River (Çetin & Demir, 2019).…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…Except for E. turgida var. granulata, all of these species were found in lowland rivers of the Sakarya Basin (Çetin & Demir, 2019;Sevindik et al, 2021;Solak et al, 2020;Tokatlı & Dayıo glu, 2011;Yüce & Gönülol, 2016) Tokatlı & Dayıo glu, 2011). The following species were identified as dominant: U. ulna in Murat Stream (Tokatlı & Dayıo glu, 2011) and in Kurtköy Creek (Sevindik et al, 2021), M. varians, M. circulare, N. radiosa and U. ulna in Felent Creek , N. radiosa in lower Sakarya River (Yüce & Gönülol, 2016) and M. varians, M. circulare and U. ulna in the upper Sakarya River (Çetin & Demir, 2019).…”
Section: Discussionmentioning
confidence: 98%
“…In fact, many studies have reported that pH and ALK are the predominant factors controlling diatom assemblage structure (DeNicola, 2000; Soininen, 2007), making diatoms effective indicators for assessing the effects of ALK due to geological formation (Bennion & Simpson, 2011; Cantonati et al, 2012). In Turkey, the pH values of streams are generally between 7 and 9, and all of the above species have been detected in the Sakarya Basin (Çetin & Demir, 2019; Sevindik et al, 2021; Solak et al, 2012; Solak et al, 2020; Solak & Wojtal, 2012; Tokatlı & Dayıoğlu, 2011; Yüce & Gönülol, 2016) and other basins in Türkiye (e.g., Çelekli et al, 2022; Çelekli & Bilgi, 2019; Kıvrak & Uygun, 2012). Moreover, A. minutissimum , C. affinis , C. neocistula and G. angustatum have also been detected in the highly alkaline lakes Hazar, Tödürge and Hafik (Kılınç & Sıvacı, 2001; Sonmez et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations